A Numerical Analysis on Flow and Heat Transfer in the Entrance Region of an Axially Rotating Pipe - Shuichi Torii; Wen-Jei Yang (International Journal of Rotating Machinery)
A numerical study is performed to investigate turbulent flow and heat transfer characteristics in the entrance region of a pipe rotating around its axis. Various different k-ε turbulence models are employed whose function consists of the Richardson number in the e model to take swirling into account. The axial rotation of the pipe suppresses thermal development and causes a substantial decrease in the Nusselt number along the flow. It is disclosed from the study that an increase in the rotation rate induces a reduction in the velocity gradient, turbulent kinetic energy and Reynolds stress in the vicinity of the wall and a substantial deformation of these radial profiles in the downstream direction. It results in both a suppression of the thermal development and an attenuation in the Nusselt number along the flow.